Investigation of Knee Arthrokinematic Changes Before and After Reconstruction of Anterior Cruciate Ligament: A Systematic Review - Ali Asghar Norasteh; Mostafa Payandeh; Zaher Mohammad Ashour (Islamic Azad University, Hamedan Branch, 2020)
Objective: The aim of this study was to investigation the arthrokinematic changes of the knee before and after the reconstruction of the anterior cruciate ligament and also to examine these changes after a period of rehabilitation exercises. Methods: In this systematic review study search was conducted in online databases of, Ebsco, Scopus, Web of Science, PEDro, Google scholar, PubMed, Science Direct, CINAHL, SPORTDiscus, EMBASE and MEDLINE from 1970 to 2020 . And keywords related to the topic were used to search for articles. Results: According to the search method, 127 articles were found that considering the inclusion criteria, 20 articles (20 English and 0 Persian) were selected. The results showed that the anterior glide in the injured knee increased significantly compared to the healthy knee. However, this arthrokinematic change was more observed in the medial epicondyle than in the lateral epicondyle. Also, among the articles, it is agreed that the highest arthrokinematic difference observed in injured persons compared to healthy individuals occurred between 15 degrees of flexion and complete extension of the knee. And Finally, the findings showed that the arthrokinematics of the knee after reconstruction, were more similar with before the reconstruction it up to a healthy knee. And also the arthrokinematic movements of the reconstructed ligament, even after a rehabilitation period, were more similar to the un reconstructed knee than to the healthy knee. Conclusion: According to the results of previous articles and being more obvious change of anterior glide, medial glide and to some extent external rotation in persons with anterior cruciate ligament rupture as well as no difference arthrokinematic knee before and after reconstruction of the anterior cruciate ligament, it seems important that rehabilitation programs and anterior cruciate ligament reconstruction techniques be planned in order to correct or prevent arthrokinematic changes are mentioned.